2015
DOI: 10.1016/j.jcat.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Structure and site evolution of molybdenum carbide catalysts upon exposure to oxygen

Abstract: a b s t r a c tAcid site densities could be reversibly tuned by a factor of $30 using an O 2 co-feed, which reversibly creates Brønsted acid sites on the carbide surface without altering the bulk crystal structure of 2-5 nm Mo 2 C crystallites. Unimolecular isopropanol (IPA) dehydration at 415 K, a probe reaction, occurred on Brønsted acid sites of these oxygen-modified carbides with an intrinsic activation energy of 93 ± 1.3 kJ mole À1 via an E 2 elimination mechanism with a kinetically-relevant step of b-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 52 publications
11
73
1
Order By: Relevance
“…The data of Table 8 also illustrate that the Mo-oxides are active for 4-MP HDO and as noted elsewhere, electrophillic coordinatively unsaturated sites present on MoO 3 and MoO 2 under reaction conditions, result in a high selectivity for C-O hydrogenolysis or DDO [21]. Previous studies have also concluded that oxygen-containing species change the surface properties of the Mo 2 C during HDO [47]. Lee et al [20] reported that the presence of D 2 O suppresses the hydrogenation ability of Mo 2 C significantly and this change is irreversible suggesting that the loss in activity is not due to competitive adsorption.…”
Section: The Analysis Of the 4-mp Hdo Reaction Kinetics Shows Very Sisupporting
confidence: 73%
“…The data of Table 8 also illustrate that the Mo-oxides are active for 4-MP HDO and as noted elsewhere, electrophillic coordinatively unsaturated sites present on MoO 3 and MoO 2 under reaction conditions, result in a high selectivity for C-O hydrogenolysis or DDO [21]. Previous studies have also concluded that oxygen-containing species change the surface properties of the Mo 2 C during HDO [47]. Lee et al [20] reported that the presence of D 2 O suppresses the hydrogenation ability of Mo 2 C significantly and this change is irreversible suggesting that the loss in activity is not due to competitive adsorption.…”
Section: The Analysis Of the 4-mp Hdo Reaction Kinetics Shows Very Sisupporting
confidence: 73%
“…In fact, in al ater study XPS was used to examine the effect of passivationo nt he Mo 2 Cs urface. [73] No Mo 2 + was detected. Instead,a bout half of the molybdenum was fully oxidized to Mo 6 + (51 %), with the remaining being partially oxidized to Mo 4 + (23 %) and Mo 3 + (26 %).…”
Section: Hdo Over Transition Metal Catalystsmentioning
confidence: 97%
“…Even though a bulk oxide or oxycarbide phase was not detected, it was postulated that surface and sub‐surface oxidation of the Mo 2 C was one of the mechanisms of catalyst deactivation. In fact, in a later study XPS was used to examine the effect of passivation on the Mo 2 C surface . No Mo 2+ was detected.…”
Section: Vapor‐phase Deoxygenation Over Novel Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Unfortunately,t he catalyst lost 50 %o fi ts activity by 4h on stream.Higher Pt loadings resulted in less deactivation. [36,37] Molybdenumc arbide-am aterialf eaturing redox sites and tunable Brønsted acidity [38][39][40] -has been shown to be ah ighly active HDO catalyst, but with low selectivity for alkylation (< 1%), [41,42] whereas nickel phosphides have shown improved selectivity for alkylation approaching 15 %. [36,37] Molybdenumc arbide-am aterialf eaturing redox sites and tunable Brønsted acidity [38][39][40] -has been shown to be ah ighly active HDO catalyst, but with low selectivity for alkylation (< 1%), [41,42] whereas nickel phosphides have shown improved selectivity for alkylation approaching 15 %.…”
Section: Introductionmentioning
confidence: 99%